How many people can live on planet earth? horizon - British Broadcasting Corporation (Hamilton, N.J. : Films for the Humanities & Sciences, 2010)
Naturalist and broadcaster Sir David Attenborough takes a look at the problems we face as a continuously growing species. Ecologists, demographers, farmers, engineers and family planning clinicians report on the enormous challenges of dealing with humans in ever increasing numbers. Improvements in social policy and global cooperation also offer hope. Should population control be the duty of each one of us?
Keywords: Population; Population -- Economic aspects; Population -- Environmental aspects